2022
DOI: 10.1097/jom.0000000000002670
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Presenteeism and Increased Risk of Divorce Among Japanese Workers

Abstract: Objective: We examined the association between the presenteeism and the risk of divorce among Japanese workers during the COVID-19 pandemic. Methods: A prospective study of 27,036 individuals was conducted starting in December 2020, with 18,560 (68.7%) participating in the follow-up in December 2021. The Work Functioning Impairment Scale (WFun) was used to measure the degree of work function impairment. Results: Compared with the group with the lowest WFun score, the odds ratio for the group with moderate WFun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It was found that between 70.6% ( 43 ) and 26% ( 38 ) of the subjects in the included studies showed sickness presenteeism. In addition, a number of factors may have also favoured presenteeism or sickness presenteeism, such as mental health-related factors [burnout ( 34 , 45 , 49 , 51 ), stress ( 33–35 , 38 , 42 , 44 , 45 , 47 , 49 ), depression ( 46 ), fear of COVID-19 ( 49 ), no well-being ( 16 , 40 ), cyberbullying ( 51 ), sleep disturbance ( 34 ), concern about having enough food ( 41 ), social isolation ( 38 ), and no resilience ( 38 )]; individual factors [poor marital relationship ( 31 ), health status ( 42 ), being young ( 38 ), attention-deficit/hyperactivity disorder symptoms ( 32 ), workers who experienced interrupted medical care ( 33 , 40 ), low physical activity ( 38 , 50 ), sedentary behaviours ( 52 ), having children ( 41 ), having health insurance ( 41 ), and having a chronic illness ( 38 )]; factors related to the situation caused by COVID-19 [confinement ( 45 ), having symptoms of respiratory infectious disease ( 48 ), not volunteering to work on the frontline ( 47 ), impact on business operations, loss of contract, and risk of bankruptcy ( 16 )]; and factors arising from working conditions [perceived organisational support ( 49 ), direct patient care ( 39 ), work functioning or task performance impairment ( 31 , 42 , 43 , 53 ), work fatigue ( 34 , 43 ), safety climate ( 22 ), workload ( 22 ), having no one to replace them ( 48 ), geographical distribution ( 48 ), transition from in-person to online modes of working ( …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that between 70.6% ( 43 ) and 26% ( 38 ) of the subjects in the included studies showed sickness presenteeism. In addition, a number of factors may have also favoured presenteeism or sickness presenteeism, such as mental health-related factors [burnout ( 34 , 45 , 49 , 51 ), stress ( 33–35 , 38 , 42 , 44 , 45 , 47 , 49 ), depression ( 46 ), fear of COVID-19 ( 49 ), no well-being ( 16 , 40 ), cyberbullying ( 51 ), sleep disturbance ( 34 ), concern about having enough food ( 41 ), social isolation ( 38 ), and no resilience ( 38 )]; individual factors [poor marital relationship ( 31 ), health status ( 42 ), being young ( 38 ), attention-deficit/hyperactivity disorder symptoms ( 32 ), workers who experienced interrupted medical care ( 33 , 40 ), low physical activity ( 38 , 50 ), sedentary behaviours ( 52 ), having children ( 41 ), having health insurance ( 41 ), and having a chronic illness ( 38 )]; factors related to the situation caused by COVID-19 [confinement ( 45 ), having symptoms of respiratory infectious disease ( 48 ), not volunteering to work on the frontline ( 47 ), impact on business operations, loss of contract, and risk of bankruptcy ( 16 )]; and factors arising from working conditions [perceived organisational support ( 49 ), direct patient care ( 39 ), work functioning or task performance impairment ( 31 , 42 , 43 , 53 ), work fatigue ( 34 , 43 ), safety climate ( 22 ), workload ( 22 ), having no one to replace them ( 48 ), geographical distribution ( 48 ), transition from in-person to online modes of working ( …”
Section: Resultsmentioning
confidence: 99%
“…Stress is one of the main contributing factors to working despite being ill which, in turn, may be one of the reasons why workers continue to work despite being ill ( 33–35 , 38 , 42 , 44 , 45 , 47 , 49 ), and in many cases workload, pressure from colleagues, and organisational culture play a part in this relationship ( 54 ). Stress was already related to sickness presenteeism prior to the COVID-19 pandemic, so it appears that COVID-19 is not the only factor that may influence sickness presenteeism as expected ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In recent years, much research in occupational health has focused on presenteeism, a condition in which workers persist in going to work despite experiencing problems and ill-health that require sick leave. [10][11][12][13][14][15] A European Working Conditions Survey reported that 41% of men and 45% of women workers reported having worked at least 1 day in the last 12 months while feeling ill. 16 The survey also found that the prevalence of presenteeism was highest in Montenegro, followed by Slovenia, Malta, Denmark, and Sweden (more than 50%), and lowest in Italy, Portugal, Poland, and Bulgaria (23%-25%). 16 Systematic differences in presenteeism according to occupation have also been found; presenteeism is more prevalent in education and the nursing and social work professions.…”
mentioning
confidence: 99%